ANALISIS PENERAPAN PASAL 31 UNDANG-UNDANG NO 24 TAHUN 2009 TENTANG KEWAJIBAN PENGGUNAAN BAHASA INDONESIA TERHADAP KONTRAK INTERNASIONAL YANG BERPEDOMAN PADA ASAS-ASAS DALAM HUKUM KONTRAK (STUDI KASUS PUTUSAN PERKARA NO.451/Pdt.G/2012/PN.Jkt.Bar) - CHANDRA HALIM (PREMISE LAW JURNAL, 2015)
Since Law No. 24/2009 on Flag, Language, State Coat of Arms, and National Anthem was enacted, Article 31, called Law of Language in paragraph 1 has confirmed the word, “Wajib” (obligatory) in using Indonesian in every contract, and paragraph 2 has also confirmed the words, “Ditulis juga” (Also written) in foreign languages when foreigners are involved in the contract. However, there are manyarguments about the use of the word, “Wajib” which is considered by some lawyers and legal practitioners to be more prioritized than the words, “Ditulis juga”. The consequence is that any contract written in a foreign language becomes weak;eventually, the Verdict of West Jakarta District Court accepted the claim of the plaintiff who used foreign language in the contract so that it was legally null andvoid. Article 31 of Law on Language has fulfilled the principle of Contract Law, referred to the Principle of Enacting Legal Provision No. 12/2011 which concerns with Legal Certainty and states that every Law should meet Legal Principle in each field, particularly which is related to a contract on Property; in this case, the Principle of Contract Law should be fulfilled. A contract which is regulated in Law on Language also meets the Principle of Contract Law, especially Article 2 of Law No. 24/2009 on Regulation in Language which is implemented in point g which states that legal certainty on evidence and validity of a contract, which uses a foreign language in Court after Law on Language was enacted, can be used as valid evidence in Court as far as the contract is original and authentic as it is stipulated in the Notarial Act and as far as it is agreed by the parties concerned, and one of them can prove it before the Court in the case of underhanded contract. Keywords: Contract, Language, Principle of Contract Law, Evidence